Mode‐stirred reverberating chamber autocorrelation function: model, multifrequency measurements and applications. Issue 5 (1st August 2015) - Sorrentino, Antonio; Gifuni, Angelo; Ferrara, Giuseppe; Migliaccio, Maurizio
Abstract : In this study, a simple model for the autocorrelation function (ACF) within a reverberating chamber (RC) is developed and verified. In particular, in a well‐stirred RC when n mechanical stirrers operate, the ACF of the total field is given by the product of n ACFs obtained when the n stirrers are singularly operated. Hence, a parameterisation of the ACF is accomplished. Accordingly, it is possible to parameterise the coherence time, T C, of the RC emulated wireless propagation channels. Experiments accomplished at the RC of the Università degli Studi di Napoli Parthenope, formerly Istituto Universitario Navale, confirm the soundness of the proposed model and its operational effectiveness.